Conflict and compromise: the Premonstratensians of Ninove (Flanders) and the laity in the twelfth century. - Bijsterveld, Arnoud-Jan A. (Negotiating Secular and Ecclesiastical Power: Western Europe in the Central Middle Ages, 1999)
Investigates what the miracle stories in the Liber miraculorum s. Cornelii Ninivensis can reveal about relations between the canons and the laity, expecially the way in which they dealt with the laity in conflicts
Keywords: ninove

De voeding in de Sint-Corneliusabdij te Ninove en het Onze-Lieve-Vrouwehospitaal te Oudenaarde in de 15e eeuw - Bruynbroeck, V. (University of Gent, 1996)
Keywords: ninove

De abdijen van Ninove en Jette (Dielegem) en hun geschil over de kerk en het kapittel van Liedekerke (1092-1180) - Van De Perre, Dirk (Analecta Praemonstratensia, 1995)
Place: Scherpenheuvel-Zichem Publisher: Commissio Historica Ordinis Praemonstratensis
Keywords: dieleghem; liedekerke; ninove

De geschiedenis van Denderwindeke. 3: Parochie en kerkelijk grondbezit tijdens de middeleeuwen inzonderheid de aanwezigheid van de abdijen van Vermand (Fr.), Vicoigne (Fr.) en Ninove (1138-1490) - Van De Perre, Dirk; Hauwe, Rik van (Het land van Aalst, 1994)
Keywords: denderwindeke; ninove; vermand; vicoigne

Een opgraving heropgegraven: Norbertijnen in Ninove, prov. Oost-Vlaanderen: interimverslag - Wouters, Werner; Peersmann, Jaak (Archeologie in Vlaanderen, 1993)
Keywords: ninove

Het altaar van Huizingen en de abdijen van Vermand, Terkameren, Ninove en Vicoigne - Van De Perre, Dirk (Analecta Praemonstratensia, 1992)
Keywords: ninove; vermand; vicoigne

Diplomatisch-paleografisch onderzoek van de oudste oorkonden van de Sint-Cornelius- en Cyprianusabdij van Ninove (1137-1300) - Van den Noortgate, Machteld (University of Gent, 1990)
Keywords: ninove